FAKTOR-FAKTOR PEMBEDA PROFITABILITAS UMKM WARUNG PECEL GARAHAN JEMBER - Dwi Perwitasari Wiryaningtyas; Tatang Ary Gumanti; Novi Puspitasari (RELASI : JURNAL EKONOMI, 2013)
Micro Small and Medium Enterprise (MSME) is a bussines activity that is able to expand employment and opportunities and very important in the economyof the Nation. MSMEs are expected to reduce the problem of poverty in Indonesia by enhancing the productivity of the poor to increase their income. This research examines the factors that differentiate the profitability of MSMEs of “warung pecel Garahan Jember”. Two groups of factors are examined, namely financial performance and non-financial performance factors. Financial performance factors examined are working capital, debt, cost of production and selling price.Non-financial factors include the level of education, the location, the old establishment, and gender. A total of 31 warung pecel are included in the analysis, and this research start March 2013 until April 2013. Mann-Whitney test analysis is used to analyze the differential factors of profitability MSME “warung pecel Garahan Jember”. Results show that only cost of production is found to be the differentiating factor of profitability of “warung pecel Garahan Jember”. And the other factors like working capital, debt, selling price, level of education, the location, the old establishment and gender are not the differential factor of profitability at “warung pecel Garahan Jember”.